Region-Specific Thermal Stability of Kelulut Honey from Indonesia: Implications for Quality and Processing - Setyawati, Inda; Meirila, Salvinia Fara; Febriyanto, Dimas; Andriyanto, Dimas (School of Life Sciences and Technology, Institut Teknologi Bandung, 2025)
Kelulut honey, produced by stingless bees (Trigona spp.), is valued for its nutritional and medicinal benefits. However, thermal treatment can alter its physicochemical properties, affecting quality and functionality. This study assessed the impact of heating at 65 °C and 121 °C for 5 minutes on Kelulut honey from seven regions in Indonesia, analyzing changes in color intensity, total dissolved solids (TDS), solubility, viscosity, water content, hydroxymethylfurfural (HMF), and acidity. At 65°C, solubility improved (e.g., Garut: 22.7 → 84.7) and TDS increased (Bogor: 77.0 % → 79.5 %), while 121 °C treatment led to significant HMF accumulation (mean: 25.91 → 40.16 mg/kg) and viscosity fluctuation. Klaten honey uniquely darkened at 121 °C, indicating regional compositional differences. Acidity dropped by up to 21% in Sumedang and Garut, while Bangka maintained stability. This study demonstrates that thermal treatment significantly influences the physicochemical quality of Kelulut honey and underscores the need for region-specific processing guidelines to maintain product integrity for food and medicinal applications, and that HMF, viscosity, and TDS could serve as reliable markers for assessing thermal effects in honey.